2022
DOI: 10.1111/ajco.13737
|View full text |Cite
|
Sign up to set email alerts
|

Teletrials, the new norm? Expert recommendations for teletrials into the future: Findings from the Clinical Oncology Society of Australia Clinical Trial Research Professionals Group Workshop

Abstract: Introduction The Australasian Teletrial Model was piloted in co‐funded sites across Australia. The purpose was to extend the reach of clinical trials using telemedicine to improve equity and access to this treatment pathway for oncology patients. Experts across Australia gathered to share the learnings of implementation so that future directions can be effective and sustainable. Methods The 1‐day workshop was attended in person and virtually. Attendees were invited to analyze and disseminate the results. Recor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…The description of CRN involvement in DCT conduct and reporting of clinical trial data comprised three different domains: network facilitation, protocol procedures and research-based care availability. The CRN role was found to be instrumental in creating relationships with participants, communities and healthcare facilities to support optimal decentralised trial function (Roberts et al, 2022: 1–10). Networking was used to troubleshoot operation-based concerns, such as equipment storage constraints and ensuring the correct physical environments were available within the community for blood draws, assessments and data collection (Coyle et al, 2022: 1031–1042; National Academies of Science, Engineering, and Medicine et al (2019); Stansbury et al, 2022: 415–422).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The description of CRN involvement in DCT conduct and reporting of clinical trial data comprised three different domains: network facilitation, protocol procedures and research-based care availability. The CRN role was found to be instrumental in creating relationships with participants, communities and healthcare facilities to support optimal decentralised trial function (Roberts et al, 2022: 1–10). Networking was used to troubleshoot operation-based concerns, such as equipment storage constraints and ensuring the correct physical environments were available within the community for blood draws, assessments and data collection (Coyle et al, 2022: 1031–1042; National Academies of Science, Engineering, and Medicine et al (2019); Stansbury et al, 2022: 415–422).…”
Section: Resultsmentioning
confidence: 99%
“…This includes the consideration of healthcare professional licensures and scope of practice, which may vary between states and countries (Fowler et al, 2021: 1–11). Geographical distance and under-resourced communities will affect staff availability, prompting trial sponsors to budget additional funds to leverage home health nursing or other professionals to support trial visit completion either in-person or via telehealth (Hawking, 2021; Roberts et al, 2022). The participant experience is also affected, as some feedback has included missing in-person interaction if more virtual components are used in the DCT model (Fowler et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Similar recommendations were echoed by the Clinical Oncology Society of Australia Clinical Trial Research Professionals Group 52 who found "being on the same page" was a key element to success of tele-trial implementation and aided by: having clear written guidelines; a united vision; and more streamlined ethics and governance processes. 52 While they reported successful examples of The Australasian Tele-Trial Model in action, areas for future improvement included having the model as routine care rather than a novelty, and diversifying income sources to reduce the reliance on pharmaceutical sponsors. 52 The primary strength of this current study was the strong representation of cancer clinical trials groups across Australia, which captured a broad range of viewpoints from clinicians, researchers, trial administrators, trial coordinators, and managers.…”
Section: Recommendationsmentioning
confidence: 99%
“…52 While they reported successful examples of The Australasian Tele-Trial Model in action, areas for future improvement included having the model as routine care rather than a novelty, and diversifying income sources to reduce the reliance on pharmaceutical sponsors. 52 The primary strength of this current study was the strong representation of cancer clinical trials groups across Australia, which captured a broad range of viewpoints from clinicians, researchers, trial administrators, trial coordinators, and managers. The focus of this investigation was CTGs operating within Australia and the Australian health care system.…”
Section: Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation